2019
DOI: 10.3390/bios9030087
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance-Based Organic Pulse Meter Sensor for Wireless Monitoring of Photoplethysmogram Signal

Abstract: This paper compares the structural design of two organic biosensors that minimize power consumption in wireless photoplethysmogram (PPG) waveform monitoring. Both devices were fabricated on the same substrate with a red organic light-emitting diode (OLED) and an organic photodiode (OPD). Both were designed with a circular OLED at the center of the device surrounded by OPD. One device had an OLED area of 0.06 cm2, while the other device had half the area. The gap distance between the OLED and OPD was 1.65 mm fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Pulse is the inner blood. The pulse waves propagating in the vascular system are reflected outside [ 6 , 7 ]. According to our pulse wave model based on the holistic view of TCM [ 8 ], the pulse phenomenon includes the flow of blood and the pulse wave carrying energy and information that spreads in the blood [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pulse is the inner blood. The pulse waves propagating in the vascular system are reflected outside [ 6 , 7 ]. According to our pulse wave model based on the holistic view of TCM [ 8 ], the pulse phenomenon includes the flow of blood and the pulse wave carrying energy and information that spreads in the blood [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is favorable not only for low‐power operation but also for preventing light from an OLED being directly coupled to the OPD without going through the human skin. Elsamnah et al experimentally compared a structure in which an OLED is wrapped around an OPD and a structure in which an OPD is wrapped around an OLED 133. It was confirmed that the power consumption of the latter is 80 times lower than that of the former, confirming the validity of the approach proposed by Lee et al These studies well illustrate that the benefits of organic technologies for wearable OPOs may not just be limited to form factors.…”
Section: Beyond Displays: Oleds For Wearable Healthcarementioning
confidence: 86%
“…The integration of OLEDs and OPDs for medicine and biodiagnostics applications has been widely reported in the last years [165]. Several reflectance-based sensors have been fabricated for wireless monitoring of the photoplethysmogram (PPG) signal [166]. In particular, Arias' research group, one of the leaders of this research area [161,167,168], exhaustively showed a real-life application of a printed array of OLEDs and OPDs [167].…”
Section: Towards Smart Integration Of Nanostructured Components For Tmentioning
confidence: 99%